PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN WORDWALL TERHADAP MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA DI KELAS III UPT SPF SD NEGERI GUNUNG SARI 1 - Desi Rahmawati Idris; Andi Ardhila Wahyudi; Hamdana Hadaming (STKIP Subang, 2025)
This research is motivated by students' lack of motivation to actively participate in mathematics learning in the classroom. Students find mathematics boring, making them less interested in actively contributing. An alternative solution to this problem is to implement interactive learning media such as wordwalls. This study aims to determine the effect of using wordwalls on student motivation in mathematics learning in third-grade students at the SPF Technical Implementation Unit (UPT SPF) at Gunung Sari 1 Public Elementary School. This research is a quantitative, quasi-experimental study. The method used is a non-equivalent control group design. The study involved two classes: a control class and an experimental class. The sample size was 41 students. Data collection techniques used a learning motivation questionnaire, observation sheets, and knowledge test sheets. Data analysis techniques used descriptive statistical analysis and inferential analysis. The results showed that the use of wordwalls on student motivation significantly increased. This was evident in the significant increase in the average learning motivation score of students in the experimental class before and after the wordwall implementation, from 54.5 to 85.09. Meanwhile, the average value of students' learning motivation in the control class using conventional learning, in the initial questionnaire test obtained 54.32 and the final questionnaire test obtained 69.11. Thus, the use of wordwall is said to have more influence on students' learning motivation compared to learning with conventional methods. The results of the hypothesis test using the Independent Sample T-Test also show that the significance value is 0.000 <0.05, which means the significance value is smaller than the predetermined alpha value of 0.05. Based on these results, it is concluded that H0 is rejected and H1 is accepted, which states that there is an effect of the use of wordwall learning media on increasing students' learning motivation in class III UPT SPF SD Negeri Gunung Sari 1.